Measuring and Evaluating the Accuracy of Mental Imagery in Young Athletes Based on Mental Response Time - Hazem Muan Abdul Ali (Wahid Hasyim University, 2026)
Visual imagination progresses through three stages. The first stage is called initial attention for learning, in which we perceive the movement as a whole but cannot see the finer details. For example, when the teacher performs, the learner sees The movement as a whole, without delving into its minute details, highlights the formula that contains the form and the ground. The second stage: the form appears more prominently than the ground, and the minute details begin to emerge It begins with understanding the whole shape, then moves on to its finer details such as the way things are held, the movement of the arm with the advance of the leg, etc. The learner begins with a holistic view of the situation and then understands its constituent elements. The third stage: In this stage, when the performance is presented to someone, they first perceive it as a whole, then examine its simpler parts and details in order to have a complete understanding of the performance. Then it is done It was summoned when needed to perform it, and the research problem, through the researcher's continuous monitoring through scientific communication, identified one of the important cases in acquiring scientific knowledge, which is The process of measuring the extent of a child's concentration towards more than one image or overlapping images in a single image, as well as the amount of time it takes a person to discover the secrets contained within a single image It is essential to delve into this field with an educated segment of the population, namely elementary school students. Furthermore, the researcher found a scarcity of scientific studies addressing such topics The research aims to identify the level of visual imagination among the student sample and to determine the extent of differences between models according to their level of difficulty. The researcher chose the descriptive approach The survey method was chosen to solve the research problem, as it was the most suitable approach to achieving the research objectives. The research population consisted of (40) emerging athletes in various types of individual and team sports The male and female students from the fifth and sixth grades were divided into (20) male students from the fifth grade and (20) female students from the sixth grade. The most important conclusion is the existence of varying levels of the sample Research into Measuring Intellectual Perception.